Investigation on the Causes of Falling From Height and Fall Protection System at Sabah - Sharma, Aldo Thirunavukarasu; Kumarason, Rasiah; Sudesh Nair, Baskara; Kishan, Gunasegaran (INTI International University, 2022)
The construction industry has been showing progressive growth over the past few years not only in terms of development of projects but also in improvement of safety measures. The bigger the projects are, the higher the risk workers faced in the construction site. This is applicable to workers who are assigned tasks on elevated positions such as high rise constructions as they possess the risk of falling from height. This project aimed at investigating the causes of falling from height as well as fall prevention and mitigation at Kota Kinabalu, Sabah, Malaysia. The research data was collected through survey where close ended questionnaires were distributed to construction companies that performed works related to elevated height. The questionnaires are based on the Likert scale where the respondent measures their level of agreement. The data was analyzed by applying Relative Importance Index (RII). The results show that the highest cause was workers not using personal protective equipment properly, followed by misjudgment and carelessness of workers as well as the usage of defective equipment. For the prevention methods, using personal protective equipment is the best solution to prevent these falls from happening besides conducting regular maintenance check on the equipment.